Teknik Pemberian dan Dosis Paket Pemupukan Pada Tanamankelapa Sawit (Elaeis guineensis jacq) di Lahan Gambut rimbo Panjang Kabupaten Kampar - Fransisca Sugiarti; Armaini '; Sukemi Indra Saputra (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This  research aims  to  determine  the  effect  of  provision  fertilizer  treatment  techniques, fertilizer doses and interactions, and also to determine the best treatment for the growth and production of oil palm plantations on peatlands in Rimbo  Panjang. The method used was Completely Randomized Design (CRD) factorial, consisting of two factors, namely the first fertilizer application techniques with 3 levels i.e  spreading systems,  burying systems and striping system. Factor II, the use of fertilizers with the level 2 as recommended (Urea=1.00kg/tree, TSP=0.88 kg/tree, MOP=0.75 kg/tree) and ½ the recommended dose  (Urea=0.50kg/tree, TSP=0.44 kg/tree, MOP=0.38 kg/tree ) with four replications, in order to obtain 24 experimental  units,  which is every experimental  unit had 2 plant  so that  the  total are  48 plants. Data were analyzed statistically by analysis of variance followed by a Duncan test New Multiple Range Test at 5% level. The parameters measured were plant height accretion, stem  girth, number of leaf, number of  flowers palm  bunches, and the number of bunches. Treatment combination with spreading fertilizer application system with ½ doses showed the best results in the accretion of plant height parameters, number of flowers palm bunches, and the number of bunches.Keywords : Palm oil, fertilizer, doses